Effect of catalyst preparation and surface modification synthesis and nanostructuring of movtenb oxide catalyst for propane oxidation to acrylic acid / Fazliana Bt Abd Hamid - Abd Hamid, Fazliana (2013)
A series of Mo1V0.3Te0.23Nb0.12 oxide catalysts were prepared using a standard recipe, with modifications to the method, i.e. addition of oxalic acid and diluents. These catalysts were subjected to activation process comprised of two different steps of calcination. The calcined samples were subjected to further modification by leaching processes in three different types of leaching media, i.e. water, nitric acid and ammonia solution. The structural, chemical, and thermal properties of the as-synthesized phase and surface modification catalyst were investigated with various characterization techniques, including X-ray diffraction (XRD),, BET surface area, X-ray fluorescence (XRF), scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM-EDX), thermogravimetric analysis coupled to mass spectroscopy (TG-MS), as well as differential scanning calorimetry (DSC). The reactivity studies have been done by temperature programmed reaction spectroscopy (TPRS) and temperature programmed reduction spectroscopy (TPR). In order to induce the catalytic activity of oxidation of propane to acrylic acid, all catalysts were further investigated for propane oxidation using high-throughput fixed bed reactor system or commonly referred to as Nanoflow. The BET surface areas for undiluted system are in the typical range of 1.0 – 10.0 m2g-1 for the MoVTeNb oxide and diluted in the range 30.0 -50.0 m2g-1. Addition of oxalic acid enhanced the surface area and catalytic activity. Different surface morphology of the catalyst obtained by low-magnification SEM images from the calcined and leaching samples indicates that leaching perturbed the surface morphologies of the catalysts. XRD result shows the calcined and leached sample to be constituted by M1 phase and M2 phases in the ratio of 50-60% and 20-30%, respectively. This also indicates that when leaching ii process occurs in oxide phase, the structure or chemical bonds were strong enough to resist breakage and thus could not be leached out easily. High-resolution TGA-MS and DSC analysis played a key role to the relevant material synthesis process. Their ability to identify the solid state of the material will further illustrate the kinetic differences of the ligand removal and gases evolved during calcination. It was proven that the preparation method, post-precipitation treatment, post calcination treatment and the activation procedure would affect the physico-chemical nature of the MoVTeNb oxide catalyst and subsequently its performance as a selective oxidation catalyst for propane to acrylic acid. Reducing agent such as oxalic acid is a good surface redox for the catalyst. Following that, a structure-activity correlation was attempted. No significant correlation was found between catalytic performance (conversion and selectivity) and M1/(M1+M2) ratios.